1998
DOI: 10.1038/sj.cdd.4400439
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors prevent changes in Bcl-2 and Bax expression and neuronal apoptosis induced by nitric oxide

Abstract: Recent studies have shown that nitric oxide (NO) donors can trigger apoptosis of neurons, and growth factors such as insulin-like growth factor-1 (IGF-1) and basic fibroblast growth factor (bFGF) can protect against NO-induced neuronal cell death. The purpose of this study was to elucidate the possible mechanisms of NO-mediated neuronal apoptosis and the neuroprotective action of these growth factors. Both IGF-1 and bFGF prevented apoptosis induced by NO donors, sodium nitroprusside (SNP) or 3-morpholinosydnon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 31 publications
4
66
0
1
Order By: Relevance
“…The result of such inhibition would be downregulation of survival factors under the control of this transcription factor, such as the antiapoptotic Bcl-2 family members. Indeed, this has been observed by a number of studies, as exogenous NO downregulates Bcl-2 but upregulates the proapoptotic protein, Bax, in neurons, 128,129 and upregulates Bad and Bax, but downregulates Bcl-2 in human colon adenocarcinoma cells. 130 In nonsmall cell lung cancer cells, it has been shown that NF-kB inhibition leads to apoptosis by increasing mitochondrial permeability, thus allowing release of cytochrome c and subsequent caspase activation (see Figure 2).…”
Section: Proapoptotic Mechanismsmentioning
confidence: 96%
“…The result of such inhibition would be downregulation of survival factors under the control of this transcription factor, such as the antiapoptotic Bcl-2 family members. Indeed, this has been observed by a number of studies, as exogenous NO downregulates Bcl-2 but upregulates the proapoptotic protein, Bax, in neurons, 128,129 and upregulates Bad and Bax, but downregulates Bcl-2 in human colon adenocarcinoma cells. 130 In nonsmall cell lung cancer cells, it has been shown that NF-kB inhibition leads to apoptosis by increasing mitochondrial permeability, thus allowing release of cytochrome c and subsequent caspase activation (see Figure 2).…”
Section: Proapoptotic Mechanismsmentioning
confidence: 96%
“…Harlan Sprague Dawley rat embryos, as described previously (18,19). Briefly, fetal hippocampi were dissected and digested with 0.25% trypsin for 20 min at room temperature in calcium/magnesium-free Hanks' balanced salt solution (Life Technologies, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Perlman et al 20 reported that a cell with a high Bax/Bcl-2 ratio was more sensitive to a given apoptotic stimuli when compared with a similar cell type with a comparatively low Bax/Bcl-2 ratio. Tamatani et al 21 hypothesized that the balance between expression of Bax and Bcl-2 proteins determined cell survival or death after an apoptotic stimulus. Therefore an increased Bax/Bcl-2 ratio is a possible indicator of PDT-induced apoptosis in LLC-IL-6 cells.…”
Section: Npe6-mediated Pdt Induced Bax Protein In Llc-il-6 Cellsmentioning
confidence: 99%